Crystal Phase Engineering Accelerates Hydrogen Reverse Spillover for Efficient Alkaline Hydrogen Production - Zhang, Jun; Chen, Xiaoyu; Wu, Bin; Guo, Xiangyang; Qu, Xianlin; Ma, Qunzhi; Wang, Ying; Li, Jiayi; Liu, Wei; Li, Xu; Cao, Liyun; Wang, Yi; et al. (Nano-Micro Letters, 2026)
Phase engineering has proved effective in enhancing electrocatalytic performance by precisely controlling crystal structures. While significant efforts have been dedicated to phase regulation of active metals, the role of crystal phase of catalyst supports in steering the hydrogen migration during hydrogen evolution reaction (HER) remains underexplored. This work systematically investigates zirconium dioxide in its monoclinic (m-ZrO2) and tetragonal (t-ZrO2) phases as supports for Ru nanoclusters. A combination of spectroscopy and theoretical calculation demonstrates strong electronic metal–support interactions and work function difference between Ru and m-ZrO2 lead to interfacial charge accumulation, accelerated water dissociation, and reverse hydrogen spillover, significantly enhancing electrocatalytic HER performance in alkaline medium. The Ru@m-ZrO2/C catalyst exhibits excellent HER activity in different electrolytes. It achieves 10 mA cm−2 with an extremely low overpotential (η10) of only 28 mV in 1 M KOH, delivering a mass activity of 2.72 A mgRu−1 (at 50 mV overpotential), which is 45 times higher than that of commercial Pt/C. The η10 values are 56, 42, and 30 mV in 0.5 M H2SO4, 1 M KOH + 2 M NaCl, and 1 M KOH + simulated seawater, respectively. Furthermore, the catalyst also demonstrates excellent stability under alkaline simulated seawater electrolysis conditions. When integrated into an anion-exchange membrane water electrolyzer, it achieves 1.0 A cm−2 at 1.76 V with stability exceeding 300 h. This work underscores the pivotal importance of support phase engineering for designing high-performance electrocatalysts for water splitting. Highlights: 1 Phase engineering of ZrO2 regulates the electronic metal–support interactions and work function difference between Ru and ZrO2, resulting in reverse hydrogen spillover, therefore enhancing electrocatalytic hydrogen evolution reaction in alkaline medium. 2 The Ru@m-ZrO2/C catalyst demonstrated a low overpotential and high mass activity (45 times that of commercial 20% Pt/C), and when integrated into an anion-exchange membrane water electrolyzer, it exhibited stable operation for over 300 hours.